Metallic and highly conducting two-dimensional atomic arrays of sulfur enabled by molybdenum disulfide nanotemplate. (December 2017) - Zhu, Shuze; Geng, Xiumei; Han, Yang; Benamara, Mourad; Chen, Liao; Li, Jingxiao; Bilgin, Ismail; Zhu, Hongli
Abstract Element sulfur in nature is an insulating solid. While it has been tested that one-dimensional sulfur chain is metallic and conducting, the investigation on two-dimensional sulfur remains elusive. We report that molybdenum disulfide layers are able to serve as the nanotemplate to facilitate the formation of two-dimensional sulfur. Density functional theory calculations suggest that confined in-between layers of molybdenum disulfide, sulfur atoms are able to form two-dimensional triangular arrays that are highly metallic. As a result, these arrays contribute to the high conductivity and metallic phase of the hybrid structures of molybdenum disulfide layers and two-dimensional sulfur arrays. The experimentally measured conductivity of such hybrid structures reaches up to 223 S/m. Multiple experimental results, including X-ray photoelectron spectroscopy (XPS), transition electron microscope (TEM), selected area electron diffraction (SAED), agree with the computational insights. Due to the excellent conductivity, the current density is linearly proportional to the scan rate until 30, 000 mV s−1 without the attendance of conductive additives. Using such hybrid structures as electrode, the two-electrode supercapacitor cells yield a power density of 106  Wh  kg−1 and energy density ~47.5 Wh kg−1 in ionic liquid electrolytes. Our findings offer new insights into using two-dimensional materials and their Van der Waals heterostructures as nanotemplates to pattern foreign atoms for unprecedented material properties. 2D hybrids: alternating layers of MoS2 and atomic sulfur Molybdenum disulfide (MoS2 ) layers can be used as templates for the formation of two-dimensional elemental sulfur. A team led by Hongli Zhu at Northeastern University used density functional theory calculations to show that the sulfur atoms sandwiched between MoS2 layers can arrange themselves into two-dimensional atomic layers, featuring a triangular array structure that results from the intrinsic triangular pattern of the parent sulfur atoms within MoS2 . These arrays are metallic, and thus contribute to the metallic phase and associated conductivity of the resulting hybrid structure composed of alternating MoS2 layers and two-dimensional sulfur layers. The experimentally synthesized compounds show conductivity up to 223 S/m. This strategy may be used for engineering of two-dimensional material hybrids by means of nano-template patterns.